Unmet psychological needs in patients with schizophrenia. Issue 1 (2nd January 2017) - Westermann, Stefan; Moritz, Steffen; Caspar, Franz; Cavelti, Marialuisa
Abstract: This online study investigated motivational incongruence (discrepancy between psychological needs and actual experiences) in patients with schizophrenia spectrum disorders and tested the hypothesis that motivational incongruence and psychotic symptoms are associated. Incongruence was associated with negative symptoms and paranoia, and was largest for "intimacy/attachment" and "avoidance of weakness". A motivational perspective on schizophrenia is thought to improve psychological therapies.